Indoor Channel Capacity Measurement of 2 x 2 MIMO Polarization Diversity Antenna - Mohamed Nasrun Osman; Mohamad Kamal A. Rahim; Mohamad Rijal Hamid; Mohd Fairus Mohd Yusoff; Mohamad Zoinol Abidin A. Aziz; Muzammil Jusoh; Muhammad Azfar Abdullah; Nursaidah Muhamad Nadzir (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
This paper presents the channel capacity investigation and the polarization reconfigurable antenna analysis for MIMO system in an indoor scenario. A single and dual-port polarization reconfigurable antenna is used at the receiver end to study the effect of polarization diversity configurations towards the achievable performance of the channel capacity. The polarization reconfigurable antennas are developed through two techniques, which are slits perturbation for single-port and feeding network modification for dual-port. The benefits offered by the designed antennas are investigated when being used as a receiver in both line-of-sight (LOS) and non-line-of-sight (NLOS) scenarios. The results show the proposed antennas are suitable to be adopted and highly potential to improve the channel capacity of the MIMO systems.